The American Nurses Association's White Paper on Nurse Staffing: Clinical and Economic Benefits of Appropriate Staffing. Issue 3 (May 2016) - N/A,
Abstract : The American Nurses Association has published a new white paper on nurse staffing Optimal Nurse Staffing to Improve Quality of Care and Patient Outcomes . All nurses should review this document to be up-to-date on the latest evidence linking appropriate nurse staffing to better outcomes for patients.